1989
DOI: 10.1152/jappl.1989.67.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Contrasts in muscle and myofibers of elite male and female bodybuilders

Abstract: Muscle cross-sectional area (CSA), fiber area, and fiber number were determined from the biceps brachii of eight elite male bodybuilders (MB) and five elite female bodybuilders (FB) who had similar training characteristics. Biceps CSA was obtained from computer tomographic scanning and corrected for noncontractile tissue. Biceps CSA was twofold greater in MB relative to FB and strongly correlated to lean body mass (R = 0.93). Biceps CSA expressed per kilogram lean body mass (LBM) or per centimeter body height … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
3

Year Published

1992
1992
2010
2010

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 13 publications
7
77
3
Order By: Relevance
“…A similar gender difference in fiber size has been reported for the biceps brachii of male and female bodybuilders (Alway et al 1989).…”
Section: Fiber Sizesupporting
confidence: 79%
See 4 more Smart Citations
“…A similar gender difference in fiber size has been reported for the biceps brachii of male and female bodybuilders (Alway et al 1989).…”
Section: Fiber Sizesupporting
confidence: 79%
“…Other studies which have corrected for connective tissue offer conflicting results. Alway et al (1989) found no significant gender difference in fiber number in the biceps brachii of male and female bodybuilders. In contrast, untrained females were found to have significantly fewer muscle fibers in the biceps brachii (MacDougall et al 1983;Sale et al 1987) and the tibialis anterior (Henriksson-Larsen 1985).…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations